1984
DOI: 10.1111/j.1944-9720.1984.tb03249.x
|View full text |Cite
|
Sign up to set email alerts
|

Computer‐Assisted Teaching and Testing of Reading and Listening

Abstract: The computer has the potential to play an important role in the teaching and testing of the receptive skills. In the area of teaching, this role need not be limited to traditional tutorial and drill-andpractice activities, and a wide range of other possibilities should be considered. The area of testing also holds promise for computer-adaptive innovations in addition to the computerization of familiar types of test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…If a teacher is conscious of his or her students' needs, the technology and materials available, and has knowledge of sound teaching and technology theories and practices, students will have greater opportunities to succeed. Though numerous studies have reported the need to further address various individual teaching and technology strategies (ChunandPlass 1996a(ChunandPlass , 1996bCrook 1994;FaerchandKaspar 1986;Felder and Henriques 1995;Field 1998;Herron 1994;Hopey et al 1995;Joiner 1986;Mayer 1997;Plass, Chun, Mayer and Leutner 1998;Pauwels 1992;Squires and McDougal1996;Stone 1988;Wyatt 1984), a more holistic approach toward technology use must be encouraged for success in the classroom. Teachers must develop an understanding of students' learning abilities or preferences and language learning needs, and they must be cognizant of the course curriculum and con tent and how technological materials can help attain course goals and objectives.…”
Section: Featurementioning
confidence: 99%
See 1 more Smart Citation
“…If a teacher is conscious of his or her students' needs, the technology and materials available, and has knowledge of sound teaching and technology theories and practices, students will have greater opportunities to succeed. Though numerous studies have reported the need to further address various individual teaching and technology strategies (ChunandPlass 1996a(ChunandPlass , 1996bCrook 1994;FaerchandKaspar 1986;Felder and Henriques 1995;Field 1998;Herron 1994;Hopey et al 1995;Joiner 1986;Mayer 1997;Plass, Chun, Mayer and Leutner 1998;Pauwels 1992;Squires and McDougal1996;Stone 1988;Wyatt 1984), a more holistic approach toward technology use must be encouraged for success in the classroom. Teachers must develop an understanding of students' learning abilities or preferences and language learning needs, and they must be cognizant of the course curriculum and con tent and how technological materials can help attain course goals and objectives.…”
Section: Featurementioning
confidence: 99%
“…Previous research suggests that careful planning in the use of technology (Field 1998;Herron 1994;Stone 1988) or awareness of students' needs and preferences (Chun and Plass 1996a;Chun and Plass 1996b;Felder and Henriques 1995;Mayer 1997;Plass, Chun, Mayer and Leutner 1998;Pouwels 1992) creates a more effective learning environment. When teachers are knowledgeable of the content used with a particular medium and its relationshiptotheircurriculum (Hopeyetal.1995;Squires and McDougal1996), orwhen theyincorporatesupportandinteraction into the classroom in relation to the technological materials used (Crook 1994;Faerch and Kaspar 1986;Joiner 1986;Wyatt 1984), this too influences learning. Though these studies already demonstrate the importance of teachers' decisions in relation to language teaching and technology, poor teacher strategiesunfortunatelycontinuein the L2classroom, primarily because many teachers are still not taught how to incorporate technologyappropriatelyinto language teaching.…”
Section: Introductionmentioning
confidence: 99%